1965
DOI: 10.1126/science.150.3701.1314
|View full text |Cite
|
Sign up to set email alerts
|

Anopheles balabacensis balabacensis Identified as Vector of Simian Malaria in Malaysia

Abstract: The mosquito Anopheles balabacensis balabacensis has been identified as a natural vector of at least two species of simian malaria in the monsoon forests of the northern Malay States. This mosquito is also a serious vector of human malaria from Viet Nam to northern Malaya. This is the first report of a mosquito which transmits both human and simian malaria in nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

1966
1966
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 3 publications
0
20
0
1
Order By: Relevance
“…Holotype adult female with associated larval and pupal exuviae on microscope slide, deposited in the NMNH. Anopheles balabacensis balabacensis of Sandosham et al (1963:46) (vector human Plasmodium); CHEONG et al (1965CHEONG et al ( :1314 Reid (1968:297) (taxonomy). Anopheles balabacensis Perlis Form of Baimai et al (1981:81) (cytogenetics, chromosome differentiation, evolution); Sucharit & Choochote (1983:90) (morphometry male genitalia, frequency gonostylus movement); Sucharit et al (1983:127) (esterase isozyme pattern, species identification); Choochote et al (1987:511) (SEM pupal setae 9-III-V).…”
Section: Anopheles (Cellia) Dirusmentioning
confidence: 99%
See 1 more Smart Citation
“…Holotype adult female with associated larval and pupal exuviae on microscope slide, deposited in the NMNH. Anopheles balabacensis balabacensis of Sandosham et al (1963:46) (vector human Plasmodium); CHEONG et al (1965CHEONG et al ( :1314 Reid (1968:297) (taxonomy). Anopheles balabacensis Perlis Form of Baimai et al (1981:81) (cytogenetics, chromosome differentiation, evolution); Sucharit & Choochote (1983:90) (morphometry male genitalia, frequency gonostylus movement); Sucharit et al (1983:127) (esterase isozyme pattern, species identification); Choochote et al (1987:511) (SEM pupal setae 9-III-V).…”
Section: Anopheles (Cellia) Dirusmentioning
confidence: 99%
“…cracens is competent to transmit simian Plasmodium in monsoon rain forest in the state of Perlis, Malaysia. Some individuals were found infected with P. cynomolgi and P. inui and the sporozoites isolated from the salivary glands caused malaria in rhesus monkey (Cheong et al 1965(Cheong et al , 1966. Studies on the susceptibility to the simian malaria parasite Plasmodium cynomolgi B strain in comparison to other Southeast Asian Anopheles showed that 77% of An.…”
Section: Anopheles (Cellia) Dirusmentioning
confidence: 99%
“…While in the northern part of peninsular Malaysia A . cracens (= A. balabacensis  =  A.dirus B) was found infected with P. cynomolgi and P. inui (Cheong et al, 1965). Laboratory studies also showed that A. cracens was a much better vector of malaria parasites compared to other species since 77% of them were infected (Scanlon, 1968).…”
Section: Vectors Of Simian Malariamentioning
confidence: 99%
“…In the sixties since molecular techniques were not available, in order to confirm species of sporozoites they were inoculated into rhesus monkeys. A. balabacensis (= A. cracens ; Sallum et al, 2005a) a vector of human malaria was incriminated as vector of P. inui (Cheong et al, 1965). …”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, se ha observado que A. hackeri es poco atraído por los humanos (34,37), mientras que A. b. introlatus y A. leucosphyrus tienen gran afinidad por los simios y humanos (39), y se ha establecido que esta última especie actúa como vector de P. knowlesi para ambos huéspedes, por lo que podría estar implicada en su transmisión a humanos. Otro candidato a vector de malaria como zoonosis, es Anopheles b. balabacensis, reconocido transmisor de malaria humana y de P. cynomolgi y P. inui (40). Los estudios realizados con ocho especies de anofeles demostraron que A. b. balabacensis era la especie más propensa a la infección por P. knowlesi (26).…”
Section: Huéspedes Y Vectores Naturalesunclassified